2019
DOI: 10.1039/c9ra07789h
|View full text |Cite
|
Sign up to set email alerts
|

Directional and velocity control of active droplets using a rigid-frame

Abstract: This paper introduces a novel directional control method of self-propelled oil droplets using an exoskeleton frame.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Yamada et al found that a single oil droplet changed into a boomerang shape when moving alone in a straight direction. 28 They succeeded to induce only the straight motion of an oil droplet by attaching it to a frame to shape it as a boomerang. A similar argument can be applied to our study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yamada et al found that a single oil droplet changed into a boomerang shape when moving alone in a straight direction. 28 They succeeded to induce only the straight motion of an oil droplet by attaching it to a frame to shape it as a boomerang. A similar argument can be applied to our study.…”
Section: Resultsmentioning
confidence: 99%
“…Because oil droplets undergo different motions when their shape is changed by external stimuli, Yamada et al achieved motion control by applying external stimuli to oil droplets. 28 In other words, when repulsive motion occurs, the charged oil droplet experiences a repulsive force from the neighboring oil droplet as a result of electrical effects, and their shapes are distorted in opposite directions. The visualization of internal convection by PIV also confirmed that such a change of shape causes each oil droplet to generate a convection flow that results in them moving in opposite directions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active droplet motion may be induced by mechanisms that break symmetry at the liquid-liquid interface as a result of chemical reactions, [137,138] surfactant adsorption or desorption, [139,140] solvent de-mixing, [141] and micelle solubilization. [131,142,143] Regardless of the origins of asymmetry, surface tension gradients (i.e., Marangoni forces) inside the droplet and within the continuous phase arise from differential surfactant concentrations that direct droplet motion opposite to that of fluid flow (Figure 18).…”
Section: Active Emulsionsmentioning
confidence: 99%
“…[24,[126][127][128][129][130][131][132] In this Section, we focus on striking examples of autonomous motion of soft synthetic systems that either arise spontaneously, referred to as active emulsions or which are stimuli-responsive, termed driven emulsions. We note that excellent descriptions of motion in conceptually related [137] Copyright 2019, Royal Society of Chemistry; B) Phase-contrast optical micrographs of the amoeba-like trajectory of O/W emulsion droplets stabilized by C16TAB, including the time-lapsed description. Scale bar, 30 μm.…”
Section: Smart Droplets and Autonomous Motionmentioning
confidence: 99%